Gaya kepemimpinan transformasional dan transaksional terhadap prestasi kerja pegawai pada dinas pertanian kabupaten buru selatan - Rahawarin, M Arsad (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2019)
This study aims to determine and analyze (1) the significance of the influence of transformational and transactional leadership styles on employee work performance and (2) the most dominant variable influencing employee performance. This research was conducted at the Office of Agriculture in South Buru Regency. The population of this study consisted of all Civil Servants (PNS) at the South Buru District Agricultural Service, namely 135 people. Sampling using the exhausting sampling method or saturated sampling. Data were analyzed by multiple linear regression. The results showed that (1) the leadership style was more dominant in the transformational leadership style, where the most influential indicator was the indicator of the idealized influence dimension, namely the leadership prioritizing the needs of subordinates, (2) based on the calculation of the average of all indicators on work performance variables, indicating a tendency positive which shows that all employees always strive to improve performance in a better direction, (3) the variable transformational leadership style and transactional leadership style have a significant influence on employee performance, (4) transformational leadership style is the most dominant variable influencing achievement employee work.Â Keywords: transformational leadership; transaction leadership; employee work performance